MAKNA TIPOGRAFI ONOMATOPOEIA PADA KOMIK â€œTIGAN NGASAK BATAVIAâ€ - Peter Ardhianto (Institut Seni Indonesia Surakarta, 2014)
Typography is an element of study in visual communication design related to letter. One of the most uniqueapplications of typography is the combination of letter with sound (onomatopoeia). Typography of onomatopoeiain visual communication design can be found in comic. The font with its own characteristic is combined withthe sound effect and then visualized as a part of text in comic â€œTigan Ngasak Bataviaâ€ by Bengkel QomikSurakarta. The problem discussed in this research is how the role of typography onomatopoeia in comicanalyzed through sound classification and semiotic approach of Roland Barthes that is denotative andconnotative. The method of qualitative research used includes interview, library study, and document. Theresult of research is that typography onomatopoeia has a function as the story determiner. The dividing ofsound source classification and sound effect in comic is completely spread. Not all of the sound effectpresented in comic â€œTigan Ngasak Bataviaâ€ shows the original sound. It exactly becomes the attractivenessand stabilization of comedy when the conflict takes place. Typography onomatopoeia in â€œTigan NgasakBataviaâ€ has a very important function that is helping audience to hear by eyes. It shows the proof that text incomic has a strong power in conveying messages.Keywords: typography, onomatopoeia, comic, visual communication